2009
DOI: 10.1111/j.1472-8206.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6‐month infliximab treatment on plasma levels of leptin and adiponectin in patients with rheumatoid arthritis

Abstract: Patients with rheumatoid arthritis (RA) appear to have increased plasma levels of leptin and adiponectin. These adipokines may be implicated in the pathophysiology of RA. Tumour necrosis factor alpha (TNF-alpha) is a potential modulator of adipokines. The effects of long-term anti-TNF treatment on plasma levels of leptin and adiponectin are not clear. The aim of this study was to assess the effects of 6-month anti-TNF treatment (infliximab) on leptin and adiponectin plasma levels in RA patients. Thirty women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
1
17
1
1
Order By: Relevance
“…In the largest so far study including 97 patients with RA, serum adiponectin was increased after 12 months of anti-TNF treatment (Nishida, Okada et al 2008), an observation also confirmed in smaller reports with the same follow-up period, implying a potential underlying mechanism for CV risk reduction by anti-TNF agents (Komai, Morita et al 2007;Serelis, Kontogianni et al 2008;Engvall, Tengstrand et al 2010). In contrast, with the exception of the Japanese study by Komai et al who revealed increased adiponectin levels as soon as 2 and 6 weeks, no changes or reduction in adiponectin levels have been reported by studies with a follow-up period of 6 months (Derdemezis, Filippatos et al 2009;Popa, Netea et al 2009). …”
Section: Racontrasting
confidence: 35%
“…In the largest so far study including 97 patients with RA, serum adiponectin was increased after 12 months of anti-TNF treatment (Nishida, Okada et al 2008), an observation also confirmed in smaller reports with the same follow-up period, implying a potential underlying mechanism for CV risk reduction by anti-TNF agents (Komai, Morita et al 2007;Serelis, Kontogianni et al 2008;Engvall, Tengstrand et al 2010). In contrast, with the exception of the Japanese study by Komai et al who revealed increased adiponectin levels as soon as 2 and 6 weeks, no changes or reduction in adiponectin levels have been reported by studies with a follow-up period of 6 months (Derdemezis, Filippatos et al 2009;Popa, Netea et al 2009). …”
Section: Racontrasting
confidence: 35%
“…Some, but not all, studies have found altered circulating levels of adipokines in patients with RA, and associations of adipokine levels with disease activity and with antiTNF treatment have been inconsistent. [60][61][62] Further research is required to elucidate the complex relationship between insulin r esistance, a dipokines and inflammation in RA.…”
Section: Diabetes and Insulin Resistancementioning
confidence: 99%
“…A study by Derdemezis et al [125] found that anti-TNF treatment effects on cardiovascular disease (CVD) risk were not regulated by changes in leptin levels. Dessein et al also argued that there was no significant relationship between leptin levels and cardiovascular risk in all patients and either female and male or black and white patients with RA.…”
Section: Effect Of Leptin On Cardiovascular Risk In Ramentioning
confidence: 99%